BOMP‐based angle estimation with polarimetric MIMO radar with spatially spread crossed‐dipole. Issue 1 (1st February 2018) - Zheng, Guimei; Zhang, Dong
Abstract : For polarimetric multi‐input multi‐output (MIMO) radar with spatially spread crossed‐dipole, this article studies the problem of joint direction of arrival (DOA) and polarisation parameter estimation based on block‐orthogonal matching pursuit (BOMP) algorithm. First, the signal model of polarimetric MIMO radar with spatially spread crossed‐dipole is established, and then the covariance matrix of the received data is calculated. Using the relationship between polarisation parameter and DOA in the crossed‐dipole, sparse dictionary matrix is constructed within only DOA parameter and it will be translated into a block sparse problem. Then, fast BOMP algorithm is used to estimate their support positions and their amplitudes. Last, DOA estimation is calculated by support positions and polarisation parameter is estimated by the amplitudes of the support positions. The proposed algorithm has three advantages. One is that overcomplete dictionary is constructed within only the DOA, which has a small computational complexity. Another one is that the problem of strong mutual coupling among collocated crossed‐dipole is solved by using the spatially spread crossed‐dipole. The last one is that the DOA and polarisation estimations can pair automatically without any additional processing. Computer simulation results demonstrate the effectiveness of the proposed algorithm.